THE DYNAMIC CONSTRUCTION OF HYBRIDITY IN THE INDONESIAN-VERSION OF GHADA KARMI'S NOVEL "IN SEARCH OF FATIMA - MENCARI FATIMA" - ANGGRAENI, Ria (2008)
This research paper is a report on a text analysis of "The Dynamic Construction of Hybridity in Indonesian-version of Ghada Karmi's Novel "In Search of Fatima - Mencari Fatima". The analysis is conducted based on these questions: (1) in what ways is hybridity constructed in the novel, and (2) what are the underlying factors of the hybridity construction. Framed by a qualitative approach in the form of a descriptive method, the close reading strategy is applied and a postcolonial theoretical framework is used to make meaning of the analysis. From the analysis it is revealed that the hybrid identity of the main character is constructed in three phases: First is English oriented identity. The main character feels and acts as English people do. Second is Palestinian oriented identity in which main character lifts up her love to Palestine. The last is shifting between Palestinian and English in which main character shifts her identity and takes ambivalence between English and Palestine. Those constructions are influenced by four factors: family condition, childhood trauma, migration to England, and living in England.